Pemberian Hukuman terhadap Kedisiplinan Siswa Kelas IX SMP - Selviani, Ade; Daheri, Mirzon; Botifar, Maria (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Punishment in school environment is one of the crucial factors in realizing students‟ disipline. Good punishment can change students to be disipline. This reseach was motivated by the low of students‟ disipline that can be seen from the students always come late,come late to the class, do not well dressed, and make a noise during learning process. One of the efforts to improve students‟ disipline was by giving educated punishment. The formulation of the problem of this research was “is there any significant influence of giving punishment toward students‟ disipline of Nineth Year Students at SMPN 4 Siak Hulu Pandau Jaya Village Siak Hulu District Kampar Regency. The objective of this reseach was to find out the influence of giving punishment towards students‟ disipline. This reseach was correlation quantitative and using simple regression analysis. Intrument that used in order to obtain the data were questionnaire and documentation. The population of this reseach were all of the students‟ of Nineth Year Students at SMPN 4 Siak Hulu that consist of 328 students and the total participants in this reseach were 77 students. After analyzing data by using SPSS 16, it obtained the probability sig was 0.000. Because of the significant was less than 0.1, 0,000<0.1, so, it can be conculded that there was low influence of giving punishment toward students‟ disipline of Nineth Year Students at SMPN 4 Siak Hulu Pandau Jaya Village Siak Hulu District Kampar Regency. This statement was proved from the coeficient determination (R Square) was 16.7% by giving punishment while 83.3% was influenced by other factors.